Taxing Tourism in Spain: Results and Recommendations - Xavier Labandeira; Alberto Gago; Fidel Picos; Miguel Rodríguez (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper analyses the foundations, possible applications and the effects of tourism taxation in Spain. The article begins with an analysis of the economic and environmental reasons for taxing tourism, which would seem to call for taxes based on the principle of benefit, for either revenue or corrective purposes. Subsequently, we describe the praxis of tourism taxation in Spain, with special mention being given to the now repealed Balearic ecotasa. Finally, the effects of two fiscal modifications with revenue or corrective objectives are studied through the use of an applied general equilibrium model developed for the Spanish economy. We thus see that a 10% tax on lodging brings in significant public receipts, increases social welfare and has no effect on the environment. On the other hand, an increase of VAT rates on tourism-related sectors could have the same effects on tourist expenditure but at the costs of greater impact for Spains economy.
Keywords: H22; L83; Q28; 330; Taxes; Tourism; Environment; Spain; Tourismus; Ökosteuer; Wohlfahrtsanalyse; Allgemeines Gleichgewicht; Spanien